GIS Communicate Emergency Preparedness Mapping: The Usability for Rural Area - Johari, Nur Syazana; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2022)
The importance of geographic information system (GIS) in daily life is well known as it is really helpful and eases the user. GIS is basically a database system with software that can analyse and display data using digitized maps and tables for planning and decision-making. Unfortunately, there are still people lacking knowledge and unreachable to apply this tool in life, especially people in rural areas. Thus, this reviewed study aimed to provide further understanding of the efficiency for decision making and planning on the usability of GIS for rural areas during emergencies. It also will be able to recognize a management information system for rural planning. This study conducts a systematic literature review (SLR) to investigate the emergency phase and type of emergency in the application of GIS. From 100 papers collected, 24 papers have been analysed under eligibility test. The result shows there is a common type of knowledge and the way it can respond to emergency preparedness. Nevertheless, there are fewer cases related to rural areas and it shows the need for more case studies and experimental research to support this promising field. In conclusion, to meet present day and future information needs for emergency preparedness, more attention needs to be given to evaluate the effectiveness of GIS in rural areas.